The Dunning-Kruger effect: subjective health perceptions on smoking behavior among older Chinese adults - Zhike Jia; Shubin Li; Zhihua Luo; Minjun Tong; Tianyue Gao (BMC, 2023)
Abstract Background The intrinsic damage and external hazards of smoking are major risk factors for poorer health and are recognized as a global health issue of concern in geriatric health. This study aims to assess the Dunning-Kruger effect through the influence of subjective health perceptions on smoking behavior in older adults. Methods This study used data from the 2018 Chinese Longitudinal Healthy Longevity Survey (N = 9,683) provided by the Center for Healthy Aging and Development Studies at Peking University. A binary logistic model was used to examine whether the Dunning-Kruger effect affects smoking behavior in older adults, and a linear probability model was used as a commentary baseline model for logistic regression to prevent measurement bias. In addition, a mediating analysis was used to examine the mechanisms through which the Dunning-Kruger effect occurs. Results Older adults often overestimated their current health status and underestimated the health risks of smoking, causing the Dunning-Kruger effect to arise from their inadequate self-perceived health (i.e., older adults are more likely to smoke when they have better self-rated health or when hypertension, cardiopathy, stroke, and diabetes have little or no impact on their daily lives). These observations can be explained by the older adults' subjective health perceptions arising from their ingenuous understanding of their health, which indirectly influences their smoking behavior to some extent. Conclusion Older adults' self-perceived health was associated with smoking behavior. Public health institutions should improve older adults' health perceptions so that they objectively understand their own health status.